Variation of macroand trace elements in organs of the blue honeysuckle subspecies of various environmental and geographic provenance when grown in the Near-Ob foreststeppe (West Siberia, Russia) - Boyarskikh Irina G. (EDP Sciences, 2021)
The variation limits and organ distribution of macroand trace elements were determined in plants of the three subspecies of Lonicera caerulea L. The leaves, as compared with the stems, were found to accumulate more of B, Са, Mg, Mo, P and Sr and less of Al, Mn, Ti and Zn. The plants of different subspecies, grown on soils of the similar chemical element composition, showed statistically significant differences in contents and organ distribution patterns of Al, Cr, Cu, Fe, Mg, Mo, Na, Ni, Pb, Si, Ti and Zn. The stems of the subspecies of the Far East provenance (L. сaerulea subsp. kamtschatica and L. сaerulea subsp. venulosa) had abnormally high contents of Al, Cr, Fe, Na, Si and Ti.